2001
DOI: 10.1097/00001813-200108000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A case of glassy cell carcinoma of the uterine cervix effectively responding to chemotherapy with paclitaxel and carboplatin

Abstract: Glassy cell carcinoma (GCC) of the uterine cervix is a highly malignant tumor and has a poor prognosis. As yet, no effective systemic chemotherapy to this tumor has been reported. Here we describe a case of recurrent GCC that responded to paclitaxel and carboplatin combination treatment. The patient, a 32-year-old woman, with clinical staging FIGO IB1 disease had a radical hysterectomy and postoperative radiotherapy. Three months after initial treatment, she had a relapse as peritoneal dissemination, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
7
0
5
Order By: Relevance
“…The other two women with adjuvant PC chemotherapy are alive in disease‐free state in for more than 4.5 years. Some reports showed that PC chemotherapy is effective for primary and recurrent GCC of the cervix 8–11 . Nasu et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two women with adjuvant PC chemotherapy are alive in disease‐free state in for more than 4.5 years. Some reports showed that PC chemotherapy is effective for primary and recurrent GCC of the cervix 8–11 . Nasu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some reports showed that PC chemotherapy is effective for primary and recurrent GCC of the cervix. [8][9][10][11] Nasu et al reported a case of glassy cell carcinoma treated using conventional radiation therapy and six courses of triweekly PC chemotherapy. 12 We also considered that adjuvant PC chemotherapy is effective for GCC.…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal therapy should be used for GCC because of the occurrence of the disease in younger patients, its rapid progression, and its poor prognosis 9 . Piura et al.…”
Section: Discussionmentioning
confidence: 99%
“…TJ therapy was selected as the regimen of NAC because Matsuura et al [11] and Hirashima et al [15] showed the usefulness of these agents against recurrent GCC. TJ therapy was selected as the regimen of NAC because Matsuura et al [11] and Hirashima et al [15] showed the usefulness of these agents against recurrent GCC.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the monthly schedule because the TJ therapy efficacy for GCC was reported with a monthly schedule [11,15] and there are some reports in which an NAC monthly schedule for cervical cancer was useful [17][18][19]. a monthly or weekly schedule.…”
Section: Discussionmentioning
confidence: 99%